2021
DOI: 10.3390/jcm10102145
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Different Concepts of Bracing in Adolescent Idiopathic Scoliosis (AIS): A Systematic Review and Meta-Analysis

Abstract: Brace treatment is the most common noninvasive treatment in adolescent idiopathic scoliosis (AIS); however it is currently not fully known whether there is a difference in effectiveness between brace types/concepts. All studies on brace treatment for AIS were searched for in PubMed and EMBASE up to January 2021. Articles that did not report on maturity of the study population were excluded. Critical appraisal was performed using the Methodological Index for Non-Randomized Studies tool (MINORS). Brace concepts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 65 publications
2
36
0
1
Order By: Relevance
“…However, full-time bracing can negatively affect patients’ perceptions of body appearance, reduce quality of life, and cause back pain [ 11 , 12 ]. Hypercorrective night-time bracing aims to provide curve correction in supine position with reduced mechanical loading [ 13 ], and has shown comparable outcomes to full-time bracing in halting the progress of spine deformity [ 14 , 15 ]. Night-time bracing may also minimise potential limitation of daytime activities compared to full-time bracing, and may facilitate better treatment acceptability and adherence for a larger proportion of patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, full-time bracing can negatively affect patients’ perceptions of body appearance, reduce quality of life, and cause back pain [ 11 , 12 ]. Hypercorrective night-time bracing aims to provide curve correction in supine position with reduced mechanical loading [ 13 ], and has shown comparable outcomes to full-time bracing in halting the progress of spine deformity [ 14 , 15 ]. Night-time bracing may also minimise potential limitation of daytime activities compared to full-time bracing, and may facilitate better treatment acceptability and adherence for a larger proportion of patients.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the results found for all types of braces ( Table 1 ) shows that not one type of brace is fundamentally better than another, after all, the results vary within the individual brace families as well. When considering the best possible care for patients, an averaging of the results, as in the study by Costa et al ( 2021 ), apparently does not support the idea of identifying the best possible treatment approach.…”
Section: Discussionmentioning
confidence: 95%
“…As Simony et al (2019) did not provide patient data with in-brace corrections of < 60%, their article was not eligible to be included in a systematic review on outcomes of different braces. Therefore, because of the selection bias, the conclusions from the review by Costa et al (2021) are not justified. Coillard et al (2014) in their randomised controlled study found a success rate of 73.1% for their patients treated with the SpineCor in a cohort with curves between 15° and 30° and a Risser stage between 0 and 2.…”
Section: Results Of Night-time Bracesmentioning
confidence: 99%
See 2 more Smart Citations